Effect of organic manures on the performance of ginger under Northern Dry Zone of Karnataka - S I Hanamashetti, M S Kulkarni, M V Sharath Pal, N K Hegde, (Journal of Spices and Aromatic Crops, 2014)
A field trial was conducted to assess the effect of different organic manures on the performance of ginger cv. Humnabad. Higher growth, yield and quality attributes were observed in the treatment receiving FYM (25 t ha-1) along with recommended dose of fertilizer (RDF) (100 : 50 : 50 kg NPK ha-1) followed by poultry manure (5 t ha-1) along with RDF. Among the treatments, significantly higher fresh rhizome yield was recorded in FYM + RDF (16.52 t ha-1) followed by poultry manure (5 t ha-1) + RDF (16.23 t ha-1) and press mud (10 t ha-1) + RDF (15.47 t ha-1). Net returns per ha ranged between Rs. 1.30 lakh (FYM+RDF) and Rs. 0.48 lakh (Neem cake @ 2 t ha-1).